DETERMINANTS OF RICE FARMING EFFICIENCY IN KARANGANYAR CENTRAL JAVA IN THE PERIOD OF ONE DECADE AFTER REFORMATION - Barokah, Umi; Rahayu, Wiwit; Agustono, Agustono; Antriyandarti, Ernoiz (Journal of Environmental Science and Sustainable Development, 2022)
One of the rice producer districts in Central Java is the Karanganyar district. The productivity of rice in Karanganyar district can still be improved because until 2010 the average productivity achieved at the farm level was still below potential or the research results were 8 ton ha-1. The low performance of farming because farmers are faced by the situation of limited production factors used in business to achieve the goal of maximizing income/welfare. The popular approach to measure the level of efficiency at the farm level is to use the frontier production function to determine technical efficiency. This study aims to determine the level of efficiency, in term of technical, allocation, and economy. This study also determines the factors that influence the technical and economic inefficiency of rice farming in Karanganyar district. This study uses Stochastic Production Frontier, by using 159 farmer respondents from 8 villages in 4 selected sub-districts. The result shows that rice farming in Karanganyar district already achieved technical and economic efficiency but has not yet for allocative efficiency. Factors of farmer's age, education, experience in rice farming, type of irrigation, and location (regional elevation) affect the technical inefficiency of rice farming in Karanganyar district significantly. While the factors that influence economic inefficiency are the type of irrigation and location. Farming households need to improve their technical efficiency, allocative efficiency, and economy efficiency.